2003
DOI: 10.1159/000070201
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Efficacy of Pantoprazole and Omeprazole in Patients with Moderate to Severe Reflux Esophagitis

Abstract: Aim: To compare the efficacy and tolerability of pantoprazole 40 mg and omeprazole MUPS 40 mg in patients with moderate to severe gastroesophageal reflux disease (GERD). Methods: In this randomized, double-blind, parallel-group, multicenter study conducted in Austria, Germany, Portugal, Switzerland and The Netherlands, patients with endoscopically confirmed moderate to severe GERD (Savary/Miller esophagitis grade II/III) were enrolled. They received a once-daily dose of either 40 mg pantoprazole or 40 mg omepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Several recent publications have indicated that the optimal dose for healing moderate/severe erosive esophagitis is 40 mg of a PPI daily [21, 22, 23, 24]. The widespread use of PPIs testifies to the symptomatic benefits that they offer also in nonerosive disease.…”
Section: Medical Therapymentioning
confidence: 99%
“…Several recent publications have indicated that the optimal dose for healing moderate/severe erosive esophagitis is 40 mg of a PPI daily [21, 22, 23, 24]. The widespread use of PPIs testifies to the symptomatic benefits that they offer also in nonerosive disease.…”
Section: Medical Therapymentioning
confidence: 99%
“…For the remaining majority of individuals who present to the primary care office with symptomatic GERD, it is safe and appropriate care to begin initial empiric PPI treatment without performing endoscopy [16]. Indeed, a recent meta-analysis comparing short-term use of PPIs has shown that, in GERD, a 40-mg daily dose of any PPI is more effective than a 20-mg dose in endoscopic healing [14], and several studies showed that PPIs are generally equivalent in terms of clinical efficacy [16, 20, 24, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…It is now widely believed that the appropriate daily doses for the treatment of moderate to severe forms of GERD are omeprazole (or its isomer esomeprazole) 40 mg, pantoprazole 40 mg, or lanscoprazole 30 mg. 25,26 Indeed, recent studies with GERD patients have demonstrated that, when used at the same dosage of 40 mg once daily (od), pantoprazole, omeprazole, and esomeprazole are 27 and to achieve high healing rates. 28,29 After 4-10 weeks of treatment, endoscopically confirmed healing was apparent in 95% of patients receiving pantoprazole (n ϭ 113) and in 90 of patients receiving esomeprazole (n ϭ 114); the difference between the two treatment groups was not statistically significant. 28 Furthermore, both drugs show similar efficacy with regard to the relief of symptoms.…”
Section: Treatment Strategiesmentioning
confidence: 97%